Karkemish sur la frontière syro-turque un marqueur au service des ambitions territoriales de l’État turc - Lorette Hehn (Frontière·s)
In 2011, 60% of the cross-border archaeological site of Jerablous for the Syrians and Karkemish for the Turks is on Turkish territory. Despite the Syrian conflict, a single archaeological mission continues to excavate until 2017, a few metres away from the Islamic State organization (Daesh), and with the acceptance of the Turkish state. The multi-millenium-old site of Karkemish on the Euphrates contains Hittite remains that the Turco-Italian mission is excavating and promoting. However, since the dismantling of the Ottoman Empire, the Turkish state has claimed the heritage of the Hittite Empire for territorial purposes. The case of the Karkemish archaeological site provides an opportunity to explore the notion of territorial marker.